Properties of Nano-Silica modified self-compacting high-volume fly ash mortar - Achara, B.E. (Medwell Journals, 2017)
The effects of adding Nano-Silica (NS) into self-compacting high volume fly ash mortar have been investigated. Five self-compacting mixtures with different NS percentage (0, 1, 2, 3 and 4) were prepared, cast and tested for fresh properties and as well as for compressive strength, accessible porosity, Interfacial Transition Zone (ITZ) and drying shrinkage. NS addition up to 2 has been found to improve hardened paste properties. However, more then 2 of NS will lead to adverse effects. © Medwell Journals, 2017.